Exploring the factor influencing the employee career planning and development in star-rated hotels in Malaysia - Jennifer Chan Kim Lian; Sharija Che Sha’ari; Jakaria Dasan (2017)
The study reports an exploratory qualitative study on career planning and development in hotels rated three to five stars in Malaysia. It explores what influences employee career planning and development in the hotel industry from the operation staff and supervisor perspectives. Specifically, it describes the factors that shape their personal career planning and development in the hotel industry. Data collection was carried out with selected hotel employees from the various departments in the three to five star-rated hotels in Malaysia from July 2015 to February 2016. A total of 151 employees were involved in data collection. Interviews and an open-ended profile accumulative technique survey were conducted with respondents as a data collection method at the respective hotels. Finding shows that majority of employee perceives positively in term of job and career opportunities and considers it quite promising due to the rapid growth of hotels. A majority of employees felt that there is a lack of proper career planning and career development provided by the hotel employers except few international chain hotels and five star rated hotels. Key factors emerged from the responses that shape and employee’s career planning and development can be divided into seven themes: 1) nature of the job – interesting and fun but also challenging ; 2) job and career opportunities available in the hotel industry; 3) work environment and flexible work hours; 4) management practices; 5) opportunities for personal development and training programs to enhance their skill, knowledge and languages; 6) Individual attitude ; 7) hotel brand names and image. These findings benefit human resource practices to develop and strengthen employee’s career planning and development. Having proper career planning and development in place may attract the right employees to remain in the hotel employment; and subsequently to reduce the staff turnover rate. It strongly suggests that human resource department should seriously look into employee’s career path and development. It also suggest that in order to attract and retain competent staffs, a paradigm shift in human resource management and practices by giving more attention to formulate relevant career paths and development strategies is required.